Combined effect of Zn2+ and Mn2+ on physiology of wood-rotting basidiomycetes. (May 2013) - Ibáñez, C; Rabinovich, M; Soubes, M; Cecchetto, G; Cerdeiras, M
Abstract : The effect of pure Zn 2+ and combined Zn 2+ and Mn 2+ supplements on the growth and ligninolytic activity of wood-rotting basidiomycetes was studied. Based on measurements of minimum inhibitory concentration and minimum decolourisation-inhibiting concentration available from cultures of Inocutis sp., Trametes versicolor and Gloeophyllum trabeum, and a comparison of such results with those obtained in previous work for P. chrysosporium and P. atropurpurascens, metal supplements were shown to inhibit fungal physiology at concentrations within the study range. Average minimum inhibitory concentration values were consistently lower for ZnSO4 than for ZnSO4 /MnSO4 (2 mM Zn 2+ ), demonstrating the antagonistic effect of the tested cations. Furthermore, because the ligninolytic system of P. atropurpurascens had shown a high tolerance to metals, its ligninolytic and germinative behaviour was compared with that of P. chrysosporium . Conidial germination was inhibited at 1 mM of Zn 2+ in the two strains, whereas extracellular activity was inhibited at concentrations above 2 mM.